A review of concrete properties under the combined effect of fatigue and corrosion from a material perspective. (10th March 2023) - Liu, Dongyun; Wang, Chao; Gonzalez-Libreros, Jaime; Guo, Tong; Cao, Jie; Tu, Yongming; Elfgren, Lennart; Sas, Gabriel
Highlights: There are coupling effects between fatigue and environmental corrosion actions. Transportation models of harmful substances in the concrete accounting for fatigue damage. Physical damage of freeze–thaw cycles and sulphate attack decrease fatigue life. Multiple alternated simulation test is a potential way to study combined effect of fatigue and corrosion. Abstract: When in use, reinforced concrete bridge structures not only experience high-frequency fatigue loading caused by passing vehicles, but also suffer from the effects of a corrosive environment. In addition to fatigue damage to reinforcement, long-term fatigue loading also causes concrete cracking and deterioration of pore structures, thereby accelerating the ingress of external corrosive substances and reducing concrete durability. Long-term exposure to a corrosive environment also reduces the performance of concrete and causes corrosion of reinforcement materials, affecting the fatigue performance of the structure. Therefore, there is a combined effect between fatigue loads and corrosion on concrete. This paper is a review of the current literature from a material perspective on the performance degradation of concrete under the combined action of fatigue loading and corrosion, that is, carbonation, chloride ion attack, freeze–thaw cycles, and sulphate attack. The paper includes (1) a description of a test method for examining the combined action of fatigue loading and corrosion, (2) a summary of performance degradation of concrete under the combined effect of fatigue loading and corrosion, and (3) an introduction to durability deterioration models considering fatigue damage, and fatigue models that can account for corrosion. Finally, potential future research on concrete under the combined effect of fatigue loading and corrosion is described.